Does JASTIP as Facilitating Condition Affect the E-Marketplace Adoption in Developing Region? - Sipahelut, Novelia; Inan, Dedi I; Juita, Ratna; Indra, Muhamad (Sistemasi: Jurnal Sistem Informasi, 2025)
E-marketplaces are expanding in developing regions but face barriers related to logistics costs and infrastructure. JASTIP, an informal proxy shopping service, has emerged as a potential solution to improve accessibility. This study examines the influence of perceived cost, social influence, hedonic motivation, and facilitating conditions on e-marketplace adoption using a modified UTAUT model analyzed through PLS-SEM with data from 185 respondents in West Papua. The findings show that hedonic motivation and social influence significantly increase user intention, perceived cost directly affects usage behavior, and facilitating conditions strengthen intention but do not directly influence usage. These results emphasize the role of JASTIP in reducing costs and improving accessibility. This study recommends improving JASTIP access and infrastructure, implementing flexible pricing policies, and promoting community-based marketing to enhance e-marketplace adoption in developing regions.